2021
DOI: 10.1007/s00004-021-00556-x
|View full text |Cite
|
Sign up to set email alerts
|

Graphical Modelling of Hoop Force Distribution for Equilibrium Analysis of Masonry Domes

Abstract: The behaviour of axisymmetric masonry shells can be simulated by a system of forces constituted by meridian forces acting in the vertical planes, and by hoop forces acting circumferentially. A crucial component for the assessment of these structures using the Modified Thrust Line Method (MTLM) is the determination of hoop forces, whose computation is strenuous, limiting the practical application of MTLM. Working around this limitation, the current research introduces a strategy to manipulate the hoop forces by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Eddy [23] made the first graphical analysis contribution to masonry domes, studying the equilibrium of a hemispherical dome through graphical reinterpretation of membrane theory. Lévy [39] and Wolfe [57] followed, with recent contributions revisiting these methods, including [29,50,58].…”
Section: From Graphic Statics To the Modern Funicular Approachesmentioning
confidence: 99%
“…Eddy [23] made the first graphical analysis contribution to masonry domes, studying the equilibrium of a hemispherical dome through graphical reinterpretation of membrane theory. Lévy [39] and Wolfe [57] followed, with recent contributions revisiting these methods, including [29,50,58].…”
Section: From Graphic Statics To the Modern Funicular Approachesmentioning
confidence: 99%
“…The resulting form is known as a catenary, which, when inverted, functions mainly through compression, eliminating bending moments (Hooke 1675;Heyman 1999;Huerta 2006a). Equilibrium in a masonry arch can be visualized using a line of thrust, which represents the path of the resultant of the compressive forces through the stone structure (Block et al 2006;Paris et al 2021). This is a rational design process in which the resulting form is a structure optimized to work under compression, and explains why stone materials with high compressive strength are especially useful.…”
Section: Inverted Catenaries and The Hotel Attractionmentioning
confidence: 99%
“…As regards the upper portion of the dome, it should be observed that the thrust line related to the independent lune would exit at some joints. Considering the action of hoop forces, for example, according to the procedure described in (Aita, Barsotti, and Bennati, 2019b) or in (Paris, Ruscica, and Mirabella Roberti, 2021), allows for finding fully statically admissible solutions for the conical dome. On the contrary, the results related to the systems formed by the conical dome and the external colonnade (or the vertical loadbearing structure), show that these structures would collapse according to the collapse mode 1, since the horizontal thrust deriving from the meridian cracking of the dome is not compatible with the rotational equilibrium.…”
Section: Equilibrium Analysis Of Conical Domesmentioning
confidence: 99%